TAURINE IN INTERNAL MEDICINE - E. M. Pokrovskaya; I. G. Gordeev; N. A. Volov; V. A. Kokorin (Российский кардиологический журнал, 2011)
The paper is focused on taurine role in various physiological and pathophysiological processes, its effects on free radical oxidation, taurine effectiveness in chronic heart failure (CHF), and the role of free radical oxidation in heart failure development. The results of numerous experimental and clinical studies are summarised.